Chromosomal G + C content evolution in yeasts: systematic interspecies differences, and GC-poor troughs at centromeres. - WOLFE, KENNETH (My University, 2010)
The G + C content at synonymous codon positions (GC3s) in genes varies along chromosomes in most eukaryotes. In Saccharomyces cerevisiae, regions of high GC3s are correlated with recombination hot spots, probably due to biased gene conversion. Here we examined how GC3s differs among groups of related yeast species in the Saccharomyces and Candida clades. The chromosomal locations of GC3s peaks and troughs are conserved among four Saccharomyces species, but we find that there have been highly consistent small shifts in their GC3s values. For instance, 84% of all S. cerevisiae genes have a lower GC3s value than their S. bayanus orthologs. There are extensive interspecies differences in the Candida clade both in the median value of GC3s (ranging from 22% to 49%) and in the variance of GC3s among genes. In three species-Candida lusitaniae, Pichia stipitis, and Yarrowia lipolytica-there is one region on each chromosome in which GC3s is markedly reduced. We propose that these GC-poor troughs indicate the positions of centromeres because in Y. lipolytica they coincide with the five experimentally identified centromeres. In P. stipitis, the troughs contain clusters of the retrotransposon Tps5. Likewise, in Debaryomyces hansenii, there is one cluster of the retrotransposon Tdh5 per chromosome, and all these clusters are located in GC-poor troughs. Locally reduced G + C content around centromeres is consistent with a model in which G + C content correlates with recombination rate, and recombination is suppressed around centromeres, although the troughs are unexpectedly wide (100-300 kb).
PUBLISHED
Keywords: Genetics; G + C content